Recent progress in cassava varietal improvement and agronomy research in Malaysia - Tan, Swee Lian; Chan, S.K. (International Center for Tropical Agriculture, 1995)
A total of four sets of seeds (totalling 5526 seeds) were recieved from CIAT during the period 1990-1993. One set (comprising 1100 hybrid seeds) originated from the Thai-CIAT program in Rayong. Evaluation and selection of seedling clones has progressed satisfactorily, and culminated in the release on August 9, 1992 of an early clone (CM3906-31) named MM 92. This cultivar is capable of yielding 30 t/ha of fresh roots on drained peat after six months, and up to 40 t/ha on mineral soils. Starch content, however, was low at 20 percent. Agronomic research included studies on the effect of spacing and fertilizer rates on the yield of Perintis (released in 1988) and MM 92 grown on peat. A long-term fertility trial on peat has now completed its ninth cropping cycle. The most significant response has been to lime applications. On mineral soils, an erosion control study over two seasons of cropping showed that natural grass or citronella contour barrier strips were most effective in reducing erosion, although statistically there were no significant differences in soil loss due to the different tillage and cropping treatments. Physiological studies on the effect of water stress (in excess and in short supply) were carried out in lysimeters and large containers, respectively. Cassava was able to withstand flooding (at 3 1/2 months) up to 3-4 days. Drought at 4 months seemed to increase the cyanide content in the root pith of the edible variety Medan. Conversely, moisture stress lasting three weeks in an 8-month crop appeared to produce the same effect in both Perintis and Medan